FORMING STUDENTS’ SPEECH BY TEACHING PHONETICS (Scientific journal of the Fergana State University, 2024)
This article is based on a comparative analysis of the alphabetical book of Uzbek, Kyrgyz, Tajik, Karakolpak, Kazakh, Turkmen and Russian languages studied in Uzbekistan, as well as the content of the ongoing work on the formation of phonetic knowledge in the process of literacy training, and the final conclusions of methods to achieve the intended results.